Building the Nigerian Palliative Care Workforce: An Interdisciplinary Distance Learning Training Program. Issue 1 (27th October 2022) - Ogbenna, Ann; Drane, Denise; Crowe, Autumn N.; Oyedele, Oluwafikewa; Hauser, Joshua; Soyannwo, Olaitan; Ogunseitan, Adeboye; Doobay-Persaud, Ashti
Background: Education and capacity building in palliative care are greatly needed in Nigeria. Currently, two institutions integrate palliative care into the undergraduate medical curriculum and no post graduate training exists. A team from the University of Lagos in Nigeria and Northwestern University in the US collaborated to design, implement, and evaluate a 12-hour virtual palliative care training program for Nigerian health professionals. Objective: This study investigated the impact of the first session of the training program on healthcare professionals' knowledge, skills, attitudes, and confidence in palliative care. Methods: The Education in Palliative and End-of-Life (EPEC) curriculum and the Kenya Hospices and Palliative Care Association (KEHPCA) curriculum were used as foundations for the program and adapted for the Nigerian context. Delivered online, the training focused on goals of palliative care, whole patient assessment, communication skills, pain management, psychosocial issues, palliative care in COVID, oncology, and HIV. A mixed-methods evaluation based on Kirkpatrick's evaluation framework was used and data were gathered from surveys and focus groups. Findings: Thirty-five health professionals completed the training. The training had a positive impact on knowledge, skills, and attitudes. Confidence in providing end-of-life care increased from 27.3% to 92.9% while confidence in prescribing medication to relieve symptoms at the end of life increased from 42.9% to 92.0%. Performance on multiple-choice knowledge tests increased by 10% (p < 0.01). All participants stated that they would recommend the program to a peer while 96.4% reported the program was relevant to the Nigerian context. Qualitative analysis suggested that the training would help participants provide more holistic care for patients, communicate better, and change how they interacted with families. Topics to be addressed in future training were identified. Conclusions: This virtual training can be an important element in palliative care capacity building in Nigeria and represents a model for global health collaboration.